1982
DOI: 10.1159/000214643
|View full text |Cite
|
Sign up to set email alerts
|

Factor VII in Liver Cirrhosis

Abstract: Factor VII activity and factor VII cross-reacting material (CRM) in plasma of patients with liver cirrhosis have been studied before and after vitamin K1 parenteral administration. Subjects were divided into two groups according to the absence (group I) or the presence (group II) of the following clinical findings: ascites, portal hypertension, encephalop-athy. Factor VII activity and CRM show a statistically significant correlation (p < 0.001) in all patients. In group II, significantly reduced lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…However, this perception is contrary to the results of several studies that have shown an increase in thromboembolic risk in cirrhotic patients [11]. Although the levels of several coagulation factors are low in cirrhosis patients [12], they also develop acquired deficiencies in the anti-coagulation factors (including protein C, protein S, and anti-thrombin III) [13]. Additionally, these patients often suffer from physical conditions which prohibit active lifestyles, thus perpetuating the risk of thromboembolism.…”
Section: Discussionmentioning
confidence: 92%
“…However, this perception is contrary to the results of several studies that have shown an increase in thromboembolic risk in cirrhotic patients [11]. Although the levels of several coagulation factors are low in cirrhosis patients [12], they also develop acquired deficiencies in the anti-coagulation factors (including protein C, protein S, and anti-thrombin III) [13]. Additionally, these patients often suffer from physical conditions which prohibit active lifestyles, thus perpetuating the risk of thromboembolism.…”
Section: Discussionmentioning
confidence: 92%